The Perfume of the Dying - O'Connell, Kim (Ars Medica, 2018)
This is a personal essay reflecting on the strange scent that becomes prevalent as the author's aunt is in the final stages of metastasized cancer and how that ushers in other sense memories of growing up under this aunt's influence.